Advancing Social Inclusion through Climate Information Services and Climate-Smart Agriculture - Gondwe, Therese; Diabate, Fatoumata; Huyer, Sophia (2025)
Social Inclusion is a results-enhancing strategy for scaling climate-resilient innovations. Intentional design and co-creation are critical to reaching marginalized and “hard-to-reach” populations. Cordinated guidance and practical tools are essential to strengthen shared understanding and consistent application of social inclusion across project activities.